2005
DOI: 10.1080/0972060x.2005.10643447
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition ofZiziphora clinopodioidesLam. From Iran

Abstract: The composition of the essential oil obtained from the dried aerial parts of Ziziphora clinopodioides Lam. (Labiatae) was analyzed by GC and GC-MS. Seventy-one components have been identified in the essential oil of Z. clinopodioides. The major constituents of the essential oil were 1,8-cineole (10.4%), iso-menthone (6.0%) and β-pinene (5.6%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
4
7
0
Order By: Relevance
“…The results of the oil yield were in accordance with Behravan et al, 9 which they reported the yield of their essential oil 0.75%, but higher levels of essential oil yields (1.1% and 0.98%) was reported by Amiri 8 and Morteza-Semnani et al, 11 respectively. Analysis of the obtained essential oil from leaves of Z. clinopodioides by GC-MS leads to the identification of eighteen components, representing 99.65% of the total essential oil (Table 1).…”
Section: Yield and Analysis Of Ziziphora Clinopodioides Essential Oilsupporting
confidence: 81%
See 2 more Smart Citations
“…The results of the oil yield were in accordance with Behravan et al, 9 which they reported the yield of their essential oil 0.75%, but higher levels of essential oil yields (1.1% and 0.98%) was reported by Amiri 8 and Morteza-Semnani et al, 11 respectively. Analysis of the obtained essential oil from leaves of Z. clinopodioides by GC-MS leads to the identification of eighteen components, representing 99.65% of the total essential oil (Table 1).…”
Section: Yield and Analysis Of Ziziphora Clinopodioides Essential Oilsupporting
confidence: 81%
“…19 In contrast with our results, Sonboli , isomenthone (6.0%) and α-pinene (5.6%) were the major components. 11 As described above, variability and diversity in the major constituents depending on numerous factors. Hence, further studies are required to investigate the chemical composition of Z. clinopodioides essential oil which grows in different parts of Iran.…”
Section: Yield and Analysis Of Ziziphora Clinopodioides Essential Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is commonly and widely applied as a flavoring agent in foods such as dairy and meat products. 14…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies on Z. clinopodioides has confirmed the presence of pulegone, 1,8‐cineole, thymol, carvacrol, p ‐cymene and limonene in this species (Morteza‐Semnani et al . ; Aghajani et al . ).…”
Section: Introductionmentioning
confidence: 99%